A systematic review of health promoting effects of consumption of whey-based fermented products on adults - Sar, Taner; Bogovic Matijasic, Bojana; Danilovic, Bojana; Gamero, Amparo; Gandía, Mónica; Krausova, Gabriela; Martínez-Villaluenga, Cristina; Peñas, Elena; Bagherzadehsurbagh, Erfan; Cemali, Özge; Santa, Dushica; Künili, Ibrahim Ender; et al. (Frontiers in Nutrition, 2025)
IntroductionFermented whey-based products show significant potential as functional foods, owing to their rich nutritional profile and the generation of bioactive compounds during fermentation. This systematic narrative review evaluates the health effects of fermented-whey consumption based on evidence from human studies in adults.MethodsA systematic literature search was conducted using electronic databases including, PubMed, Scopus, and Cochrane Library for studies published between 1.1.1970 and 31.12.2024. All human clinical studies conducted with adults over 18 years old were included in this study. Inclusion criteria were randomized controlled trials and clinical studies involving adults consuming fermented whey products. Data extraction and quality assessment were performed using CADIMA software and standardized protocols. Studies identified by the search strategy and extracted data were screened independently by 2 reviewers using the CADIMA software. Risk of bias was assessed using the Risk of Bias 2 tool.ResultsAfter screening 1852 titles and abstracts and assessing 20 articles for eligibility, a total of 12 human intervention studies met the inclusion criteria and were included in the systematic narrative review. Consumption of fermented whey products was associated with improvements in muscle mass, glycemic control, lipid profiles (notably triglycerides and LDL cholesterol), immune function (e.g., increased natural killer cell activity), and reductions in oxidative stress and inflammation. Some studies also reported benefits for gastrointestinal and urinary tract health. The health effects were attributed to increased bioavailability of branched-chain amino acids, bioactive peptides, and microbial metabolites such as exopolysaccharides and short-chain fatty acids. Most interventions were well tolerated, with no serious adverse effects reported.ConclusionFermented whey products demonstrate promising health benefits across multiple physiological systems. While current evidence supports their use as functional food ingredients, further large-scale, long-term clinical trials are needed to confirm efficacy and elucidate mechanisms of action. Fermented whey appears to be a safe and versatile option for enhancing adult nutrition and health.